Paciente masculino de 50 años con insuficiencia respiratoria. - Chacón Hernández, Cesar Ariolfo (2021)
The current clinical case is based on a 50-year-old male patient with respiratory failure, who presented with symptoms of dyspnea, nasal flaring, exhaustion and a non-productive cough for more than 3 days, dyspnea appeared 12 hours ago. He does not present hyperthermia, does not present hypotension, or arterial hypertension. The present case was carried out based on the general objective of determining the benefit of oxygen therapy in respiratory failure, in addition diagnostic methods were used, the severity of bronchial asthma was identified and the effective treatment of respiratory failure was determined. Respiratory failure in the inability to develop correct breathing when this abnormality occurs, carbon dioxide can be retained causing hypercapnia, when this type of syndrome exists it is important to establish a treatment plan and definitive diagnosis of what is the cause or factor of risk. There are two main types of respiratory failure in which it can be divided into hypoxemic and hypercapnic; hypoxemic is defined by the partial saturation of oxygen in the blood below 90%, while breathing an inspired fraction of oxygen (FiO2), while hypercapnic respiratory failure is characterized by alveolar hypoventilation, in addition to being associated with respiratory acidosis, It can be caused when there is a pathology associated with respiratory failure, such as; neuromuscular, COPD or can be caused by a drug overdose. High-flow oxygen therapy was used as a treatment for respiratory failure, and the administration of drugs such as atrovent, dexamethasone, sodium chloride, which were used by nebulization for greater effect on the patient's airway. Once these treatments were used, respiratory failure was reduced, oxygen saturation improved, improving the stability of the patient.